Functional fitness level of military college cadets - S.S. Fedak; V.M. Afonin; O.R. Nebozhuk; V.B. Lashta; I.V. Romaniv; V.V. Dzyama; I.V. Pylypchak (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to work out and study influence of author's physical training program on functional fitness of military college officers. Material: in the research 83 3rd year cadets of military college participated (experimental group, n=41; control group, n=42), of age 19-21 years. The cadets' functional state was registered by indicators of Shtange's test, Genchi test, test of Ruffiet - Dixon, Cooper's test. The volume of trainings was 4 hours a week. Results: it was found that the acting training programs do not permit to completely prepare combat soldier's organism for fulfillment of his tasks. We also found the purposefulness of special exercises and means' application in physical trainings, which would be approached by their structure to military officers' professional actions. Conclusions: it is recommended to conduct training with complex combining of different physical training sections (accelerated motion, overcoming obstacle course, hand-to-hand fighting and etc.) with special means ( armor vest, tactic unloading system, helmet, weapon, gas mask, training grenades and so on).